THE JAVANESE DIALECTS USED BY ENGLISH DEPARTMENT STUDENTS OF UNIVERSITAS BRAWIJAYA FROM MADIUN AND SURABAYA - MEGAWATI, TIARA PUSPA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Dialects, Javanese dialects, Madiun and Surabaya English Department Students. Language and society cannot be separated. Because of the language, people can communicate with each another. There is a relationship between language and the region in which they live. Because of relationship between language and region, people who live in one region have their own dialect. From that explanation, sociolinguistics do not be separate with dialect. This study examines the Javanese dialect used by English Department students from Madiun and Surabaya. The problems of the study in this study are what are the words in Madiun and Surabaya Javanese dialects used by English Department Students the theory proposed by Chaer (2012) about lexical, and what are Javanese levels of the words are used the theory proposed by Aji (2013). This study uses qualitative approach since the data is presented in the form of words rather than numbers. The data are Javanese words in Madiun dialect and in Surabaya dialect and the data source is Javanese utterances produced by students of English department in 2010 grade. The researcher collects the data by making question for interview and making topic to have conversation, and then recording the conversation done by the respondent. Then, transcribing the recording and analyzing them and finally drawing a conclusion. The researcher found 29 utterances that contain lexicon in Javanese using Madiun and Surabaya dialects. There are twenty two words of Ngoko Kasar, seven words of Ngoko Alus and no word of Madya used in Surabaya dialect. It happens because the societies of Surabaya do not use Madya language to communicate with teenagers or the younger persons. And the researcher also found twenty six words of Ngoko Alus language, three words of Madya language, and no word of Ngoko Kasar language in Madiun dialects. The societies of Madiun do not use Ngoko Kasar language because they think that it is so rude to use at the daily communication. Ngoko Alus language is used to communicate with teenagers or the younger person than the speaker is.The conclusion is that Surabaya dialects are ruder than the societies of Madiun dialect. The next researcher is recommended to conduct the study of dialects using the other theories. The researcher also suggests the next researchers to conduct a research on other regional dialects for example; Sundanese dialects, Chinese dialects, Batak dialects, to broaden the understanding of dialects.